Advances in management of hepatorenal syndrome. Issue 5 (September 2021) - Khemichian, Saro; Francoz, Claire; Nadim, Mitra K.
Abstract : Purpose of review: Hepatorenal syndrome (HRS) is encountered frequently in patients with end-stage liver disease and remains an important cause of morbidity and mortality in this patient population. This review will focus and provide updates on pathophysiology, assessment of kidney function, new definitions, and treatment and prevention of HRS. Recent findings: Pathophysiology of HRS has been elucidated more recently and in addition to hemodynamic changes, the role of systemic inflammatory response contributes significantly to this process. Assessment of kidney function in patients with liver cirrhosis remains challenging. Novel glomerular filtration rate equations have been developed in patients with liver disease to better estimate kidney function and changes made in the definition of acute kidney injury (AKI), which are more aligned with KDIGO criteria for AKI. Vasoconstrictors, especially terlipressin, along with albumin remain the mainstay of pharmacological treatment of HRS-AKI. Biomarkers have been useful in differentiating ATN from HRS at an early stage. Summary: HRS remains a significant cause of morbidity and mortality for patients with end-stage liver disease. Newer understanding of mechanisms in development and pathophysiology of HRS have helped with elucidation of the disease process.